Nitrogen fertilization in biomass sorghum improves the yield and quality of soybeans grains grown in succession in long-term management systems - da Silva, Gustavo Ferreira [UNESP] (2024)
Soil management systems have already been shown to be able to promote changes in edaphic properties, yield, and sustainability of soybean production systems. Additionally, nitrogen fertilization in production systems has shown a potential to increase production and fertilizer use efficiency. However, there is still a need to investigate the changes that these soil management and production systems can promote in grain quality. Thus, the aim of this research was to evaluate the soybean grains quality as a function of nitrogen fertilization applied to the sorghum crop, preceding soybean grown in the summer season in conventional tillage (CT) and no-tillage (NT). The experiment was carried out in the field, in the 2019/20, 2020/21 and 2021/22 seasons crops, in a randomized block design, in a split-plot scheme, with four replications. The plots were composed by soil management systems (CT and NT) and the subplots by nitrogen fertilization in sorghum (0, 50, and 100 kg ha−1 of N). At the dose of 50 kg ha−1 of N, the crude protein contents in the soybean grains were 15% and 38% higher than the other doses in CT and NT, respectively, resulting in increases in protein yield of around 34% and 45%, respectively. Nitrogen fertilization at a dose of 50 kg ha−1 applied as a top dressing to sorghum promotes a higher quality of soybeans grown in succession, in CT and NT. However, soil management under NT with 50 kg ha−1 of N results in higher yield and grain quality, allowing greater financial return and efficiency in the use of nitrogen fertilization. The nitrogen fertilization at a rate of 50 kg ha−1 as top dressing in the sorghum crop results in increased productivity and quality of soybean grains grown in succession, with the most significant results observed in the no-tillage system. Our results show that nitrogen fertilization in a production system with sorghum and soybean, mainly in no-tillage, is capable of maximizing the use of nitrogen fertilizer, increasing the yield and quality of soybeans grains and maximizing the financial return of the farmer. Our results also show that pricing soybeans based on the protein content in the grain can a tool to increase agronomic efficiency in food production. Results of this research also allow us to visualize the importance of a consolidated no-tillage system, to obtain greater yield, grain quality and financial return from agricultural activity. Thus, emphasizing the significance of conservation management and nitrogen fertilization in an agricultural production system to enhance the yield and quality of soybean grains.